The effect of student centered pharmacology teaching in the form of clinical case scenario among M.B.B.S students - Britto, G. Francis; Subash, K. R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Pharmacology teaching by conventional method is by didactic lectures and practical sessions. To cultivate interest and motivate students towards self directed learning, the best tool in teaching learning methodology available is case based learning. Aims and objective of the study was to analyze the effectiveness and acceptance of case based learning (CBL) of pharmacology among M.B.B.S Students. Methods: The second year M.B.B.S Students of the academic year 2014 and 2015 were enrolled in the study. Clinical case scenario was formulated as modules based on the common clinical cases which the student observe and encounter in clinical postings in wards. The students were divided in to four groups, 30 in each group with one facilitator. Each module of case based learning was evaluated with pre test and post test. The student perception was recorded by a five point likert scale feedback questionnaire at the end of the study. Results: The post test scores in all modules revealed significant improvement in student’s performance by CBL method when compared using “paired t test”. Majority of the students preferred more CBL sessions for rest of the academic year. Conclusions: Students centred pharmacology teaching by CBL method creates self-directed learning environment to explore more for better understanding and application of the theoretical knowledge gained towards clinical practice.